Bidikmisi: Analisis Pelaksanaan Program Beasiswa Pendidikan Tinggi - Rusi Rusmiati Aliyyah; Sri Wahyuni Ulfah; Endang Sri Budi Herawati; Reza Rachmadtullah; Andes Safarandes Asmara (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The study aims to determine the implementation of the BM scholarship program. This study uses a qualitative case study method by analyzing program implementation according to criteria. The results showed that the implementation of the BM program was in accordance with the planning criteria for the program. The program manager structure has roles in accordance with its tasks and functions. The mechanism for selecting program participants, fostering program participants, monitoring and evaluation as well as reporting on program implementation went very well. In conclusion, the program implementing HR is very supportive of BM so that the duties and responsibilities of program managers are very well realized. Keywords: Bidikmisi Scholarship, Program Implementation, Higher Education